2016
DOI: 10.1016/j.jsb.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Human sirtuins: Structures and flexibility

Abstract: In recent years, sirtuins (SIRTs), members of histone deacetylases (HDACs) class III, have been found to modulate cellular processes related to the development of human aging-related pathologies (i.e. cancer, neurodegeneration, metabolic disorders). Several crystallographic structures and computational studies have shed light into their catalytic mechanism of action, identifying also the structural elements for the design of selective drug candidates. In this review, we first aim at summarizing the structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 66 publications
0
33
0
Order By: Relevance
“…Sirtuins may thus be distinguishable by their diverse subcellular localizations. SIRT1, SIRT6, and SIRT7 are mainly located in the nucleus [5,6], while SIRT3, SIRT4, and SIRT5 are mainly located in the mitochondria. SIRT1 and SIRT5 have been found in the cytoplasm [3,7].…”
Section: Overview Of the Sirtuin Familymentioning
confidence: 99%
“…Sirtuins may thus be distinguishable by their diverse subcellular localizations. SIRT1, SIRT6, and SIRT7 are mainly located in the nucleus [5,6], while SIRT3, SIRT4, and SIRT5 are mainly located in the mitochondria. SIRT1 and SIRT5 have been found in the cytoplasm [3,7].…”
Section: Overview Of the Sirtuin Familymentioning
confidence: 99%
“…Resveratrol is an activator of Sirt1 [33][34][35][36][37][38]. Whether does resveratrol activate the Shh signaling via Sirt1?…”
Section: Discussionmentioning
confidence: 99%
“…Activated Sirt1 by resveratrol has anti-aging, neuroprotective and neurogenetic and anti-hypertrophic scar effects [33][34][35][36][37][38][39]. Tiberi et al reported that BCL6/BCOR/SIRT1 complex inhibited medulloblastoma and enhanced neurogenesis by suppressing the Shh signaling [40].…”
Section: Introductionmentioning
confidence: 99%
“…After the balanced system was observed, production was continued for 50 ns. The ptraj program from AmberTools and VMD was used to perform trajectory analysis of the molecular dynamic simulation results [15]. The parameters analyzed were RMSD and root mean square fluctuation (RMSF), and the hydrogen bond conditions were analyzed using VMD program.…”
Section: Molecular Dynamicsmentioning
confidence: 99%
“…Therefore, the present study used an in silico study with molecular docking and dynamic simulations of the SIRT1 enzyme (PDB IDs 4ZZI, 4ZZJ, 4ZZH, and 5BTR) to determine the bonding interactions of SIRT1 required for ligand selectivity and selective identification of bond interactions and target bond interactions with biological function [14,15].…”
Section: Introductionmentioning
confidence: 99%